2013
DOI: 10.1002/dev.21140
|View full text |Cite
|
Sign up to set email alerts
|

Reacquisition, reinstatement, and renewal of a conditioned taste aversion in preweanling rats

Abstract: Pavlovian extinction is defined as a reduction of the conditioned response (CR) as a consequence of repeated and nonreinforced presentations of the conditioned stimulus (CS). This phenomenon has been explained through two nonexclusive associative hypotheses. One of them proposes that the CS-unconditioned stimulus (US) association is weakened during extinction, while the second one explains extinction by the formation of a new inhibitory association between the CS, and the US (CS-noUS) which competes with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 53 publications
8
22
0
Order By: Relevance
“…This effect was only found when subjects were trained and tested in a salient context with an explicit olfactory component (Experiments 2 and 4a), which is consistent with prior research showing the relevance of olfactory contexts in regulating behavior and learning in preweanling rats (Brasser and Spear 2004;Revillo et al 2015). Consistent with the present results, we have previously reported reinstatement, renewal, and more rapid reacquisition in preweanling rats using a conditioned taste aversion paradigm (Revillo et al 2014a), and renewal and spontaneous recovery using fear conditioning procedures (Revillo et al 2013(Revillo et al , 2014b. Taken together, all of these findings suggest the possibility of recovering an extinguished CR during infancy by means of a variety of procedures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This effect was only found when subjects were trained and tested in a salient context with an explicit olfactory component (Experiments 2 and 4a), which is consistent with prior research showing the relevance of olfactory contexts in regulating behavior and learning in preweanling rats (Brasser and Spear 2004;Revillo et al 2015). Consistent with the present results, we have previously reported reinstatement, renewal, and more rapid reacquisition in preweanling rats using a conditioned taste aversion paradigm (Revillo et al 2014a), and renewal and spontaneous recovery using fear conditioning procedures (Revillo et al 2013(Revillo et al , 2014b. Taken together, all of these findings suggest the possibility of recovering an extinguished CR during infancy by means of a variety of procedures.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, in some of these studies the authors did not find recovery of the CR once it was extinguished (Kim and Richardson 2010), while others have reported renewal, more rapid reacquisition, and reinstatement in taste aversion learning (Revillo et al 2014a), and spontaneous recovery (Revillo et al 2014b) and renewal (Revillo et al 2013 in fear conditioning. Those authors that did not find recovery of the extinguished CR suggested that in infancy, extinction is a qualitatively different phenomenon to that observed in adulthood, and that during infancy it results in erasure of the CS -US association instead of the production of new learning (Kim and Richardson 2010).…”
mentioning
confidence: 99%
“…An additional body of work, in tasks that allow the separation of the contextual learning from the fearful learning, suggests that contextual learning can occur around PD 17, but cannot be utilized for subsequent fear conditioning, latent inhibition or renewal until after weaning [26][28], although this may depend upon the specific nature of the context and task [29], [30]. Similar findings have now also been reported in spatial navigation tasks [31].…”
Section: Introductionsupporting
confidence: 61%
“…Theoretically, it may be regarded as a sort of renewal upon the return to the context of reinforcement (Bouton, Woods, & Pineño, 2004). In studies of taste aversion induced by LiCl injection, there are some theoretical and empirical debates on the speed of reacquisition (e.g., Aguado, de Brugada, & Hall, 2001;Brooks, Bower, Anderson, & Palmatier, 2003;Carlton, Mitchell, & Schachtman, 1996;Danguir & Nicolaidis, 1977;Hart, Bourne, & Schachtman, 1995;Löpez, Cantotra, & Aguado, 2004;Revusky & Coombes, 1979;Schachtman et al, 2000;Revillo et al, 2014). Here, we will not be addressing any argument as to what the proper control for assessing the speed of reacquisition should be.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that taste aversion acquired by rats following ingestion of a target taste accompanied by a LiCl injection, which was subsequently extinguished by a mere exposure to the target taste alone, could be renewed by changing background contexts (e.g., Bernal-Gamboa et al, 2012;Fujiwara et al, 2012;Revillo, Castello, Paglini, & Arias, 2014;Rosas & Bouton, 1997Rosas, García-Guetiérrez, & Callejas-Aguilera, 2007). To the best of our knowledge, however, there have been no published studies on the renewal of taste aversion acquired by rats in the generalized bait-shyness paradigm.…”
Section: Experiments 1a 1b and 1cmentioning
confidence: 99%